123 Supporting A Learning System in Paediatric Emergency Pathways; Using Organisational Comparisons, Serious Incidents and Near Miss Events To Improve The Diagnosis And Treatment Of Testicular Torsion. (12th October 2021) - Winters, D; Mehmi, A; Menzies-Wilson, R; Folkard, S; Ryan, K; Sevdalis, N; Green, J
Abstract: Introduction: Scrotal pain is a common presentation to the emergency department requiring prompt investigation and management to identify testicular torsion. Using national data we aim to identify key suboptimal areas in the acute diagnosis and management of testicular torsion with a view to improving outcomes. Method: A freedom of information request was made to all Trusts in England that manage testicular torsion. Serious Incidents (SI's) were analysed to see if those with Paediatric Emergency Departments fared better than those without. In addition, a qualitative thematic analysis of the NHS England Strategic Executive Information System database from 2007-2019 was undertaken, identifying common themes associated with orchidectomies and 'near miss' events in children. Results: 304 serious incidents were returned with 62 Orchidectomies and 242 Near Miss Events. Misdiagnosis of symptomatic testicle was not significant when comparing ED to specialists (OR = 1.46, p = 0.3842). Atypical presentation resulting in orchidectomy was significant when comparing ED to specialists (OR = 6, p = 0.0355). Near miss events are due to a variety of factors. There was no statistical significance in incidents when comparing ED's caring for all ages with Paediatric EDs U = 807.5, z = -1.124, p = 0.261. Conclusions: There's a need for education in ED about atypical presentation of testicular torsion and examination of scrotum in cases of lower abdominal pain. It's also vital that specialist teams are cognisant of the standard operating procedures relevant to scrotal pain. Finally, there should be a drive for annual audit in Urology and ED units with regards to testicular torsion as SI's may be under-reported.